Evaluation of the impact of the patriotic education website (OTEPMI) of the “Ignacio Agramonte Loynaz” University - Alonso Porro, Karely; Márquez Lizaso, Rolando; Benavides Bailón, Jeovanny Moisés (Transformación, 2024)
Objective: The paper aims at completing a comprehensive assessment of OTEPMI website, devised as didactic tool for patriotic education at the University of Camagüey. Methods: The authors rely on analysis and synthesis, inductive and deductive methods and documentary analysis to process information, identifying characteristic features, recognizing relations between structural components and reaching at partial and final conclusions. They submit the website to the assessment of expertise professionals and survey professors and students to explore satisfaction.Results: The findings describe the website devised for patriotic education at the University of Camagüey, the results of it professional assessment, and information related to teachers’ and students’ satisfaction.Conclusions: Both professors and students graded the website functional descriptors between useful and indispensable, the satisfaction questionaries’ given confirmed such results.
Keywords: Technology education; program evaluation; patriotic education; Citizenship education